Efeito da adição de clorexidina nas propriedades adesiva e antibacteriana de um cimento de ionômero de vidro de alta viscosidade - Becci, Ana Carolina de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate the bond strength to dentin and the microbial composition of the biofilm formed over a high-viscosity GIC to which chlorhexidine diacetate (CHX) was added at different concentrations. CHX was mixed with GIC powder at 0.5%, 1% and 2% (w/w). GIC without CHX was used as control. In the first study, eighty human third molars were used. They had an area of dentin exposed on the occlusal surface. Half of the specimens were kept sound and the other half was subjected to artificial caries induction. In each dentin surface a cylindrical specimen with 1 mm in diameter and 1 mm in weight (n=10 per group) was made. They were kept at 37°C and 100% humidity for 24 hours and tested for microshear. The results were analyzed using Kruskal-Wallis and Mann Whitney tests (α = 0.05). In the second study, volunteers (n=8) wore palatal appliances containing specimens with 4mm in diameter and 1mm in weight. The material with increasing concentrations of chlorhexidine were tested by all volunteers for a period of 7 days each, with a wasout period of 15 days. After each step, the biofilm formed on the specimens were collected and analyzed. Data from total anaerobic microorganisms, total streptococci, mutans streptococci and lactobacilli were analyzed by repeated measures ANOVA followed by Tukey test. The significance level was set at 5%. There were no statistical significant differences between bond strength of sound and caries-affected dentin (p> 0.05). Groups GIC, GIC+CHX 0.5% and GIC+CHX 1% showed bond strength statistically similar (p> 0.05) and higher than GIC+CHX 2% group (p ≤ 0.025). Microbial counts showed statistical significant differences among groups only for lactobacilli (p<0.05). GIC+CHX 2% presented higher mean counts than GIC and GIC + CHX 0.5% (p<0.05). In conclusion, the addition of CHX diacetate 0.5% and 1% did not change bond strength of a high-viscosity GIC in...

Este estudo teve como objetivo avaliar a resistência de união à dentina e a composição microbiana do biofilme formado sobre um CIV de alta viscosidade ao qual foi adicionado diacetato de CLX em diferentes concentrações. A CLX foi misturada ao pó do CIV nas concentrações de 0,5%, 1% e 2%. O CIV sem CLX foi usado como controle. No primeiro estudo, foram utilizados 80 terceiros molares, que tiveram uma superfície de dentina exposta na face oclusal. Metade dos dentes foi mantida hígida e a outra metade foi submetida à indução artificial de cárie. Em cada superfície dentinária, foi confeccionado um espécime cilíndrico com 1mm de diâmetro x 1 mm de altura (n=10 por grupo). Estes foram mantidos a 37ºC com 100% de umidade por 24 horas, e submetidos ao teste de microcisalhamento. Os resultados foram analisados pelos testes de Kruskall-Wallis e Mann Whitney (α=0,05). No segundo estudo, voluntários (n=8) usaram dispositivos palatinos contendo espécimes (4 mm de diâmetro x 1 mm de altura). Os materiais foram testados por todos os voluntários na ordem crescente de concentração de CLX por um período de 7 dias e com intervalo de descanso de 15 dias entre elas. O biofilme formado sobre os espécimes foi coletado e analisado. Os dados referentes às contagens de microrganismos anaeróbios totais, estreptococos totais, estreptococos do grupo mutans e lactobacilos foram submetidos à análise de variância de medidas repetidas complementada pelo teste de Tukey. O nível de significância adotado foi de 5% . Não houve diferença estatística na resistência de união entre a dentina hígida e afetada (p>0,05). Os grupos CIV, CIV+CLX 0,5% e CIV+CLX 1% apresentaram resistência de união estatisticamente semelhante (p>0,05), e superior ao CIV+CLX 2% (p≤0,025). Houve diferença entre as médias de contagem de microrganismos apenas para o lactobacilos (p<0,05), sendo estas significativamente maiores...
Keywords: Clorexidina; Cimentos de ionômeros de vidro; Biofilme; Biofilms